Citizens' distrust of government and their protest responses in a contingent valuation study of urban heritage trees in Guangzhou, China. (15th May 2015) - Chen, Wendy Y.; Hua, Junyi
Abstract: Protest response is a common aspect of contingent valuation (CV) studies, which has attracted growing attention from scholars worldwide. Distrust of government, understood as one of the major reasons for protest response, has been prevalent across transitional China experiencing dramatic changes in its economy, society and natural environment. Citizen distrust of government would significantly hinder the efficiency and validity of the contingent valuation method (CVM) application focusing on the provision of public environmental and ecological goods in China, as a large proportion of protest responses might be induced. Hitherto little has been done to link residents' trust in government to their environmental behaviors in developing and transitional economies like China where CVM has been increasingly applied to generate meaningful and reliable information for integrating both ecological and socioeconomic perspectives into policy decisions. This study aims to investigate the discrepancies between protest responses induced by distrust of government and non-protest responses, using the contingent valuation of heritage trees in Guangzhou as a case. The combination of a set of debriefing questions and several attitudinal questions is employed in the questionnaire. Based on logit analysis and discriminant analysis, it has been found that protestors who distrust government and non-protestors share similar salient values associated with urban heritage trees in Guangzhou, especially their distinctive historical and cultural values, in comparison with ordinary urban trees. Residents with low familiarity with heritage trees (who rarely visit sites with heritage trees, know little about management and conservation techniques, and consider present management to be ineffective) are likely to act as protesters with the "distrust of government" belief. Only if more opportunities are provided for residents to obtain access to urban heritage tree sites, more information (about urban heritage trees and other environmental and ecological goods) is disseminated, and more effective management is implemented, can better governmental trust be developed and stronger public participation and support secured. The results of this study can shed light on understanding protest responses in CV studies and improving the reliability and efficiency of CVM in China and other developing countries where a low level of trust in government prevails. Highlights: Distrust of government is a major reason for protest responses in CV studies. The discrepancies between protestors with distrust belief and non-protestors have been investigated. Protestors with distrust belief and non-protestors share similar salient values associated with urban heritage trees. Low familiarity with urban heritage trees would induce distrust of government and protest responses.